Testing of planar hydrogenated amorphous silicon sensors with charge selective contacts for the construction of 3D-detectors. (1st March 2022) - Menichelli, M.; Bizzarri, M.; Boscardin, M.; Caprai, M.; Caricato, A.P.; Cirrone, G.A.P.; Crivellari, M.; Cupparo, I.; Cuttone, G.; Dunand, S.; Fanò, L.; Hammad, O.; et al.
Abstract: Hydrogenated Amorphous Silicon (a-Si:H) is a well known material for its intrinsic radiation hardness and is primarily utilized in solar cells as well as for particle detection and dosimetry. Planar p-i-n diode detectors are fabricated entirely by means of intrinsic and doped PECVD of a mixture of Silane (SiH4 ) and molecular hydrogen. In order to develop 3D detector geometries using a-Si:H, two options for the junction fabrication have been considered: ion implantation and charge selective contacts through atomic layer deposition. In order to test the functionality of the charge selective contact electrodes, planar detectors have been fabricated utilizing this technique. In this paper, we provide a general overview of the 3D fabrication project followed by the results of leakage current measurements and X-ray dosimetric tests performed on planar diodes containing charge selective contacts to investigate the feasibility of the charge selective contact methodology for integration with the proposed 3D detector architectures.